The Morphological Identification of Fungi Causing Cocoa Fruit Rot Disease and Inhibition Test of Bacillus spp. Against the Fungus in Vitro - Elfina, Yetti; ., Irfandri; Sabirunah, Aisyah; Wijayanto, Dimas; Rizqi, Alfin; Mu'arif, Maulana (JURNAL BUDIDAYA PERTANIAN, 2024)
Cocoa plants in Nagari Bunga Tanjung, West Sumatra Province, are infected with cocoa pod rot disease by the fungal pathogen Phytophthora palmivora and this causes serious problems if not appropriately controlled. Therefore, Bacillus spp testing needs to be undertaken to obtain Bacillus spp that were more capable of inhibiting the growth of the pathogen. The research was conducted at the Plant Disease Laboratory, Faculty of Agriculture, Riau University in February-June 2024. Completely Randomized Design (CRD) were used in this emerimantal study with 5 treatments and 4 replicates so that 20 there were experimental units. The treatments given were: B0 : Without Bacillus spp, B1 : Bacillus amyloliquefaciens, B2: Bacillus cereus, B3: Bacillus pseudomycoides and B4: Bacillus velezensis. Variables observed were the macroscopic and microscopic characteristics of Phytophthora palmivora, the diameter of pathogenic colonies after the application of Bacillus spp. and the inhibition of Bacillus spp. bacteria against Phytophthora palmivora. Further testing was done through Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results of the research conducted showed that the cause of cocoa fruit rot disease in Nagari Bungo Tanjuang is Phytophthora palmivora based on morphological characteristics. All Bacillus spp. namely: Bacillus cereus, Bacillus amyloliquefaciens, Bacillus pseudomycoides, and Bacillus velezensis were able to inhibit the growth of Phytophthora palmivora fungus in vitro. Bacillus cereus, Bacillus amyloliquefaciens, Bacillus pseudomycoides, and Bacillus velezensis were able to inhibit the growth of Phytophthora palmivora in vitro. Phytophthora palmivora with inhibition power of 38.89%, 40.28%, 43.33%, 77.78%, respectively.